2021
DOI: 10.1037/sgd0000451
|View full text |Cite
|
Sign up to set email alerts
|

Why LGBTQ+ campus resource centers are essential.

Abstract: Lesbian, gay, bisexual, transgender, queer, and additional marginalized genders and sexualities. LG-BTQϩ campus resource centers provide essential services for college and university communities and are increasingly necessary in light of the ongoing and reverberating impacts of the COVID-19 pandemic. This commentary describes specific needs of LGBTQϩ student populations in accessing health care, psychosocial support, advocacy, and academic support in the context of the COVID-19 pandemic. We briefly review curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…This should also include making all non-TGNB specific therapy groups inclusive of TGNB individuals, for example, by making it common practice to invite sharing of pronouns and making space for TGNB identities. Such suggestions align with those of Gilbert et al (2020).…”
Section: Discussionsupporting
confidence: 79%
“…This should also include making all non-TGNB specific therapy groups inclusive of TGNB individuals, for example, by making it common practice to invite sharing of pronouns and making space for TGNB identities. Such suggestions align with those of Gilbert et al (2020).…”
Section: Discussionsupporting
confidence: 79%
“…To date, a few published studies have explored the impact of the COVID-19 pandemic on LGBTQ individuals. Scholarship has explored the impact of COVID-19 on LGBT people in Chile (Barrientos et al, 2021) and Nigeria (Oginni et al, 2021), how LGBT youth and emerging adults found support during the COVID-19 pandemic (Fish et al, 2020; Woznicki et al, 2020), LGBTQ palliative care during the COVID-19 pandemic (Rosa et al, 2020), mental health needs and psychological distress of LGBT youth and college students (Gonzales et al, 2020; Gilbert et al, 2020; Hawke et al, 2021; Hunt et al, 2021), the role of internalized stigma in predicting protective health behaviors (Solomon et al, 2021), the perceived threat of COVID-19 with sexual minority women (Potter et al, 2020), and sleep disturbances of sexual minority men during the COVID-19 pandemic (Millar et al, 2020).…”
Section: Lgbtq Minority Stress and Resiliencementioning
confidence: 99%
“…A majority of the sexual minority participants in our study identified as bisexual. Although this is not true for all college students, particularly those living in larger bodies, there are opportunities to explore and embrace one’s marginalized identities on college campuses via cultural and identity-based resource centers and student organizations (e.g., diversity services; LGBTQ+ campus resource centers; Gilbert et al, 2021), which may provide some additional protection against suicide risk. Such levels of self-acceptance and identity affirmation may explain why a recent study of community and college adults found that social support and emotion regulation, independently and in sequence, mediated the association between sexual minority status and suicide attempts (Chang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%